Transnational Terrorist Recruitment : Evidence from Daesh Personnel Records - Brockmeyer, Anne; Do, Quy-Toan; Joubert, Clement; Bhatia, Kartika; Abdel Jelil, Mohamed (MIT Press, 2022)
Global terrorist organizations attract radicalized individuals across borders and constitute a threat for both sending and receiving countries. We use unique personnel records from the Islamic State in Iraq and the Levant (Daesh) to show that unemployment in sending countries is associated with the number of transnational terrorist recruits from these countries. The relationship is spatially heterogeneous, which is most plausibly attributable to travel costs. We argue that poor labor market opportunities generally push more individuals to join terrorist organizations, but at the same time limit their ability to do so when longer travel distances imply higher migration costs.